HUBUNGAN GAYA KEPEMIMPINAN KEPALA RUANGAN DENGAN KEPUASAN KERJA PERAWAT PELAKSANA DI ROYAL PRIMA HOSPITAL TAHUN 2016 - karmila kaban (Jurnal Maternitas Kebidanan, 2018)
The leadership style of the head of the room is the behavioral pattern of the head of the room space that is shown to influence the mind of the executing nurse based on the leadership behavior itself. Consisting of 6 kinds of democratic, participatory, autocratic and laissez-faire, situational and delegation. Job satisfaction is a positive attitude toward work in a person. Divided into 2 categories: satisfied and dissatisfied. The purpose of this study was to identify the relationship of head leadership style with job satisfaction of nurses at Royal Prima Hospital. This research is Quantitative. The sampling technique used is part of the population, where the population is 259 and the sample is taken as much as 120 nurses. The result of chi square test shows that there is a relationship of leadership style with the nurse work satisfaction at Royal Prima Hospital with the degree of meaning (59.970> 2) = value p = 0.001. It is advisable for the head of the room to continue applying a democratic leadership style so that the nurse will be able to provide optimal nursing care without having to feel the head of the room doing strict supervision.